Research on the Relationship between GSCM and Enterprise Performance: a Multidimensional Analysis based on Manufacturing Industry - Cheng, Lingna (International Journal of Global Economics and Management, 2024)
Green supply chain management (GSCM) refers to focusing on green environmental protection and reducing the pollution of the whole industrial chain in the process of enterprise production and cooperation with upstream and downstream, which helps to realize the coordinated development of the economy and the environment. With the increasing global environmental problems, GSCM has become an inevitable trend for the transformation and upgrading of manufacturing enterprises in China. However, the relationship between GSCM and enterprise performance has not yet reached a consensus. This paper adopted a multi-case study research method to analyze the GSCM performance of manufacturing enterprises from multiple dimensions. The results showed that GSCM enhances enterprise performance by improving economic, environmental and social performance. These performance improvements not only contribute to the long-term development of the enterprise, but also enhance the competitiveness of the enterprise and the sustainability of its development. This study would improve and enrich the theory of GSCM, and enhance the theoretical basis for enterprises to improve their competitiveness and realize sustainable development. At the same time, the study can provide reference for the government and relevant organizations to formulate and implement relevant policies, and provide important theoretical guidance and decision-making reference for realizing the high-quality development of China’s economy.